THE ANALYSIS OF THE MARRIAGE AGE ACCORDING TO THE MARRIAGE LAW OF THE REPUBLIC OF INDONESIA NO. 16 OF 2019 - Akhmad Zaki Yamani (Adisam Publisher, 2024)
This study aims to describe the age of marriage in Act No. 16 of 2019 on the Amendment of the Marriage Law No. 1 of 1974. In this study the author uses a normative jurisprudence approach, which is a study based on library research in order to obtain secondary data in the field of law. The method is used to dig the foundations, norms, theories and legal opinions relevant to research issues through inventory and study of primary, secondary, and tertiary law materials. Law No. 1 of 1974 dominated many elements of religion/belief and reality living in society. On the other hand, this Act No. 1 of 1974 seeks to reinforce the principles contained in the Pancasila and the Basic Law of the Republic of Indonesia of 1945. From the point of view of this Act, the change in the age of marriage in Act No. 16 of 2019 is a reform of the marriage law. This reform of the age of marriage does not preclude the provisions of article 2, paragraphs (1) and (2) which stipulate that marriage shall be legally performed according to the law of religion, also must be recorded by the authority.